2016
DOI: 10.1016/j.matbio.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Truncated amelogenin and LRAP transgenes improve Amelx null mouse enamel

Abstract: Amelogenin is the most abundant enamel protein involved in enamel mineralization. Our goal was to determine whether all three regions of amelogenin (N-terminus, C-terminus, central core) are required for enamel formation. Amelogenin RNA is alternatively spliced, resulting in at least 16 different amelogenin isoforms in mice, with M180 and LRAP expressed most abundantly. Soon after secretion by ameloblasts, M180 is cleaved by MMP20 resulting in C-terminal truncated (CTRNC) amelogenin. We aimed to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Micro-CT and FE-SEM analyses of the mineral formed by PND1 molar germs after a 9-day culture revealed an increase in enamel volume with LRAP(+P) while it was not increased by LRAP(–P) treatment. Rescue experiments with recombinant plasmid encoding LRAP in amelogenin KO mice, have shown that LRAP contributes to final enamel thickness and prism organization (Gibson et al, 2011 ; Xia et al, 2016 ). It can be speculated from our data, that in these mice LRAP is present under its phosphorylated form.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT and FE-SEM analyses of the mineral formed by PND1 molar germs after a 9-day culture revealed an increase in enamel volume with LRAP(+P) while it was not increased by LRAP(–P) treatment. Rescue experiments with recombinant plasmid encoding LRAP in amelogenin KO mice, have shown that LRAP contributes to final enamel thickness and prism organization (Gibson et al, 2011 ; Xia et al, 2016 ). It can be speculated from our data, that in these mice LRAP is present under its phosphorylated form.…”
Section: Discussionmentioning
confidence: 99%
“… Significant differences (p < 0.05) are indicated as follows: w from WT; x from Amelogenin KO; 3o from M180Tg/CTRNCTg/LRAPTg/KO (++); 3t from M180Tg/CTRNCTg/LRAPTg/KO (+); 2o from M180Tg/CTRNCTg/KO (++); 2t from M180Tg/CTRNCTg/KO (+) . a Gibson et al ( 2011 ); b Xia et al ( 2016 ) , c Li et al ( 2008 ) , d Pugach et al ( 2013 ) , e Pugach et al ( 2010 ) , f Chen et al ( 2003 ) , g Gibson et al ( 2009 ) . …”
Section: Resultsmentioning
confidence: 99%
“…Both recent in vitro and in vivo evidence suggest that CTRNC plays an important role in enamel mineralization (Kwak et al, 2009 , 2011 ; Martinez-Avila et al, 2011 ; Xia et al, 2016 ). In vitro studies have suggested a role of full-length amelogenin in the control of mineral phase, specifically the stabilization of amorphous mineral phases such as amorphous calcium phosphate (ACP), and alignment of forming crystallites (Kwak et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations